THE APPLICATION OF NORMALITY RULE AND ENERGY BALANCE EQUATIONS FOR NORMALLY CONSOLIDATED CLAYS - A. S. Balasubramaniam; E. Y. N. Oh; M. Bolton (Lowland Technology International, 2005)
In this paper, it is reiterated that the Roscoe and Poorooshasb (1963) formulation of the stress strain behaviour of normally consolidated clays is indeed in a more generalized form which is easily amenable to incorporate deformations under various degrees of drainage and can be extended to include cyclic loading and time effects beyond the primary phase of deformation. Also, the formulation can be used for stress states below the state boundary surface to include lightly overconsolidated and heavily overconsolidated clays. Particularly, it is shown here that Cam Clay model of Roscoe et al. (1963) and Modified Cam Clay model of Roscoe and Burland (1968) as based on energy balance equations and the normality concept can be considered as the special cases of the original formulation of Roscoe and Poorooshasb (1963). In order to achieve this, all theories are presented in similar mathematical forms, adopting the same formulation of Roscoe and Poorooshasb (1963). Modified Cam Clay Model of Roscoe and Burland, and the Roscoe and Poorooshasb theory made identical predictions of the shape of the state boundary surface, the pore pressure development during undrained behaviour, and the volumetric strain in the drained tests for all types of applied stress paths. Also, Modified Cam Clay model was only successful in predicting the shear strains along radial stress paths. For non-radial stress paths, Modified Cam Clay model needed an additional set of constant deviator stress yield loci, and when such a set was incorporated, the prediction from Modified Cam Clay model was the same as the original prediction of Roscoe and Poorooshasb (1963).